HC27 Generic Soil Profile Database - Koo, Jawoo; Dimes, John (International Food Policy Research Institute, 2013)
The HC27 soil profile database consists of generic soil profiles developed by John Dimes and Jawoo Koo. The 27 soil profiles were generated based on three criteria that crop models are most responsive to: texture, rooting depth (proxy of water availability), and organic carbon content (proxy of fertility). Three levels for each category were classified using the boundary conditions based on the meta-analysis of WISE 1.1 soil profiles measured at crop land areas in Sub-Saharan Africa. There are multiple ways to utilize these generic soil profiles in crop modeling applications, especially when soil measurement data is not available for the study site. For example, (1) users can choose the one that best matches the soil typically found in the study area by following the decision tree of three multiple-choice questions and use it as a starting point, or (2) users can run models with all 27 soil profiles for a given study site to create a possible range of simulation results, which can be narrowed down later as more site-specific information becomes available. These generic soil profiles does not replace existing soil mapping efforts nor site-specific soil measurements. Instead this approach addresses the need for a set of reasonably representative and prototypical soil profiles in certain types of crop modeling applications (e.g., global-scale modeling studies). Due to the nature of being "generic," there will be applications for which the use of HC27 is not desirable, especially where detailed soil property dynamics beyond the three criteria are emphasized.